On 'Systematic' Reviews of Research Literatures: A 'narrative' response to Evans & Benefield: British Educational Research Journal: Vol 27, No 5 - Hammersley, Martyn (British Educational Research Journal, 2001)
The production of ‘systematic’ reviews of research findings has recently come to be treated as a priority in the field of education, and other areas too. Such reviews are believed to play an important role in making evidence from research available in a usable form to policy‐makers and practitioners. This article examines the assumptions about research, and about the task of reviewing, which are built into the concept of systematic review. In addition, attention is given to the likely consequences of the priority now being given to this type of review.